La Chambre des communes, le système électoral et l'usage du référendum - Lemieux, Vincent (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The reform of the House of Commons must remain faithful to the main objective of making it more representative. None of the reasons given in support of the present electoral system can erase the fundamental injustice of it, at least for those who believe that in a representative democracy elections primarily serve to represent voters, and not just to form a government. The present system must be replaced by a more proportionate system.